PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN PERAWAT (Kasus Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru) - Silaban, Evant Johanes; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how the effect of work motivation and job satisfaction to nurse commitment (caseof RSIA Eria Bunda Pekanbaru).This research method is descriptive and quantitative using SPSS 19 program, wherein the samples used are nurse of RSIA Eria Bunda Pekanbaru with respondents as many 69 people. For a sampling technique used census method. The data collection is done through questioners and interviews.The results of the analysis using the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test , t test and F test so it can be seen that variable work motivation to nurse commitment RSIA Eria Bunda Pekanbaru, that job satisfaction significantly effect to nurse commitment RSIA Eria Bunda Pekanbaru, and significant effect between society together work motivation and job satisfaction to nurse commitment RSIA Eria Bunda Pekanbaru.Keywords:Work Motivation, Job Satisfaction, Organizational Commitment.